Minocycline increases the life span and motor activity and decreases lipid peroxidation in manganese treated Drosophila melanogaster. - Bonilla, E.; Contreras, R.; Medina-Leendertz, S.; Mora, M.; Villalobos, V.; Bravo, Y. (Toxicology, 2012)
The objective of this study was to investigate the effect of Minocycline in the life span, motor activity, and lipid peroxidation of Drosophila melanogaster treated with manganese. Two days after emerging from the pupa male wild-type D. melanogaster were fed for 13 days with corn media containing 15 mM manganese. Then, they were divided in six groups of 300 flies each: group (a) remained treated with manganese (Mn group); group (b) began treatment with Minocycline (0.05 mM) (Mn-Minocycline group); group (c) received no additional treatment (Mn-no treatment group); group (d) simultaneously fed with manganese and Minocycline (Mn+Minocycline group). Additionally, a control (group e) with no treatment and another group (f) fed only with Minocycline after emerging from the pupa were added. All the manganese treated flies (group a) were dead on the 25th day. The life span in group f (101.66±1.33 days, mean S.E.M.) and of group b (97.00±3.46 days) were similar, but in both cases it was significantly higher than in group e (68.33±1.76 days), group c (67.05±2.30 days) and in those of group d (37.33±0.88). Manganese (groups a and d) decreased motor activity in D. melanogaster. In the Minocycline fed flies (groups b and f) a higher motor activity was detected. In Mn-Minocycline and Mn+Minocycline treated flies a significant decrease of MDA levels was detected when compared to the Minocycline group indicating that Minocycline and Mn appear to have a synergistic effect. In conclusion, Minocycline increased the life span and motor activity and decreased MDA formation of manganese treated D. melanogaster, probably by an inhibition of the production of reactive oxygen species. Manganese also exerted an antioxidant effect as shown by the significant decrease of MDA levels when compared to control flies.